2018
DOI: 10.1108/jsm-09-2017-0321
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the application of co-design to transformative service research

Abstract: Exploring the application of co-design to transformative service research Abstract PurposeThis study investigates in a transformative service research (TSR) context how users can be involved through co-design and what contributions they can make during this process. Design/methodology/approachA six-step co-design process was used to plan and facilitate two co-design sessions that involved a total of 24 participants. The collected data include field notes, transcripts from group discussions, recordings of idea … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 50 publications
(102 reference statements)
0
53
0
Order By: Relevance
“…Collaborations with stakeholders allow program developers to tap in to the unique perspectives and insights held by various stakeholders [26] whose interests are varied. Discrepancies between expert and user views exist in the context of parent alcohol programs [94], suggesting expert designed programs may be failing to meet the unique needs of parents. Future program efforts should seek to include multiple stakeholder perspectives beyond the end user group to identify and acknowledge multiple views and resolve possible conflicts and discrepancies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Collaborations with stakeholders allow program developers to tap in to the unique perspectives and insights held by various stakeholders [26] whose interests are varied. Discrepancies between expert and user views exist in the context of parent alcohol programs [94], suggesting expert designed programs may be failing to meet the unique needs of parents. Future program efforts should seek to include multiple stakeholder perspectives beyond the end user group to identify and acknowledge multiple views and resolve possible conflicts and discrepancies.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is suggested that researchers consider novel methods that allow stakeholders to actively contribute during the design process as opposed to being passive participants. For example, empowering stakeholders through active collaborations such as co-design methods that provide stakeholder with the tools and a voice to design behaviour change programs of value to them [94].…”
Section: Discussionmentioning
confidence: 99%
“…Study 1 sought to examine the usefulness of ethnographic fieldwork as a form of “empathy building” employed to overcome challenges associated with the front-end stages of the co-design process. Previous studies (Dietrich et al, 2017; Hurley et al, 2018) reported conducting literature reviews to complete the resourcing for their co-design studies. However, due to underrepresentation of BoP citizens in the literature (Martin & Hill, 2011), and BoP citizen heterogeneity (Prahalad, 2012), adopting this approach was unlikely to be effective.…”
Section: Discussionmentioning
confidence: 99%
“…Collaboration represented by the prefix "co" implying partnership and equality Union/collaboration of stakeholders (researchers and non-researchers) [83,84];"mutual knowledge exchange" [44]; "common understanding" [66]; shared vision and decision-making; meaningful engagement with participants [47,62]; equal voice and a collective vision [54,60] Activity Ideation "generate" [18,83], "explore" [85]; "brainstorm ideas" [49], "provoke discussion" [44,78]; reflect on how to meet community needs, solve problems and improve service delivery [58,61,62,86,87] Activity Designing taking of ideas (generated in the co-ideation phase); planning of the production of concrete outcomes (products, services or programs) [41,66] Activity Implementing participation of stakeholders in the delivery of services and programs [42] Activity Evaluating usability testing of prototypes and products [47] and state actors and the public to assess the quality of public services [70,86]; provide constructive feedback on services, interventions or products to researchers [56]; feedback may be collected through the administration of pre-and post-initiative questionnaires or engagement in focus groups [53,59]; feedback is collected and used to improve services [56]…”
Section: Activitymentioning
confidence: 99%